CORRELATION BETWEEN COFFEE CONSUMPTION AND SLEEP QUALITY WITH PREHYPERTENSION IN FINAL YEAR UNIVERSITAS AIRLANGGA STUDENTS: Hubungan Konsumsi Kopi dan Kualitas Tidur dengan Kejadian Prehipertensi pada Mahasiswa Universitas Airlangga Tingkat Akhir - Ratna Nur Fitrya, Diela; Bunga Lorenza, Fadelia; Yovita Hendrati, Lucia; Mohamed Gomaa Nasr, Nayla (Jurnal Berkala Epidemiologi, 2024)
Background: The number of prehypertension patients will always be higher than hypertension patients; this is supported by the prevalence of prehypertension being 48.40% according to JNC 7, and hypertension being 34.10% according to Basic Health Research in 2018. Coffee consumption and sleep quality were risk factors that are closely related to the lifestyle of students, this is also reinforced by the number of 24-hour coffee outlets that are open around Universitas Airlangga. Purpose: This aim of this study is to analyze the relationship between coffee consumption and sleep quality on the incidence of prehypertension in final year Universitas Airlangga students. Methods: This type of research is a quantitative study with a cross-sectional study design and uses the Chi-square test. The samples consisted of 146 people, which were taken using a simple random sampling method. Data collection was carried out through an online questionnaire. This study involved coffee consumption and sleep quality as independent variables and the incidence of prehypertension in final year Universitas Airlangga students as the dependent variable. Results: There is a correlation between coffee consumption (p=0.00) and sleep quality (p=0.01) with prehypertension in final year Universitas Airlangga students. Coffee consumption has a 2,47 times greater risk and sleep quality has a 2,09 times greater risk of prehypertension in final year Universitas Airlangga students. Conclusion: Poor coffee consumption and sleep quality are related with prehypertension in final year Universitas Airlangga students.